2021
DOI: 10.1371/journal.pone.0256142
|View full text |Cite
|
Sign up to set email alerts
|

Persisting symptoms three to eight months after non-hospitalized COVID-19, a prospective cohort study

Abstract: Long-COVID-19 is a proposed syndrome negatively affecting the health of COVID-19 patients. We present data on self-rated health three to eight months after laboratory confirmed COVID-19 disease compared to a control group of SARS-CoV-2 negative patients. We followed a cohort of 8786 non-hospitalized patients who were invited after SARS-CoV-2 testing between February 1 and April 15, 2020 (794 positive, 7229 negative). Participants answered online surveys at baseline and follow-up including questions on demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
6
28
1
Order By: Relevance
“…25 Subsequently, evidence is emerging on the substantial burden of PASC among communitydwelling persons who represent the majority of persons with COVID-19. 26 Our results are consistent with reports on enduring PASC in non-hospitalized patients, 27 including reports of fatigue as the most common PASC. 28 12 Investment in cardiac-related PASC research is equally important to inform potential therapeutic strategies for PASC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…25 Subsequently, evidence is emerging on the substantial burden of PASC among communitydwelling persons who represent the majority of persons with COVID-19. 26 Our results are consistent with reports on enduring PASC in non-hospitalized patients, 27 including reports of fatigue as the most common PASC. 28 12 Investment in cardiac-related PASC research is equally important to inform potential therapeutic strategies for PASC.…”
Section: Discussionsupporting
confidence: 90%
“…25 Subsequently, evidence is emerging on the substantial burden of PASC among community-dwelling persons who represent the majority of persons with COVID-19. 26 Our results are consistent with reports on enduring PASC in non-hospitalized patients, 27 including reports of fatigue as the most common PASC. 28 In our analyses, we observed that among persons with cardiac-related PASC symptoms, those who were hospitalized, 88% reported severe fatigue, lasting well over 6 months since recovery from acute COVID-19 infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 42 Three to 8 months from onset, another study showed that 36% of non‐hospitalized COVID‐19 patients reported worsened health, while only 18% of SARS‐CoV‐2 − patients reported a similar deterioration, suggesting a long‐term burden of COVID‐19 that may last months beyond initial infection. 8 Altogether, our study patients displayed a greater symptom burden at follow‐up than other published reports. It is possible that patients who came to our clinic had more severe long‐COVID syndrome at baseline relative to the average non‐hospitalized “long hauler,” which influenced their decision to seek care.…”
Section: Discussionmentioning
confidence: 48%
“… 2 , 3 , 4 Neurologic manifestations of PASC (Neuro‐PASC) often occur in people who had mild initial respiratory symptoms and never required hospitalization for pneumonia or hypoxemia, known as COVID‐19 “long haulers.” 5 While most studies have focused on long‐COVID syndrome in previously hospitalized patients, most COVID‐19 patients have a mild initial presentation. However, there have been few investigations into long‐term effects of COVID‐19 in non‐hospitalized “long haulers.” 6 , 7 , 8 Additionally, while SARS‐CoV‐2 vaccination can reduce rates of COVID‐19 and death, its effect on long‐COVID syndrome remains unclear. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%